Familial Alzheimer's disease and inherited prion disease in the UK are poorly ascertained. Issue 9 (27th August 2010) - Stevens, J C; Beck, J; Lukic, A; Ryan, N; Abbs, S; Collinge, J; Fox, N C; Mead, S
Abstract : Aims: To ascertain the frequency and geographical distribution of patients diagnosed with known genetic causes of Alzheimer's disease (AD) and inherited prion disease (IPD) in the UK 2001–2005. By comparison with frequencies predicted from published population studies, to estimate the proportion of patients with these conditions who are being accurately diagnosed. Methods: All the positive diagnostic test results (from both genetic testing centres) were identified for mutations in presenilin-1 ( PSEN1 ), presenilin-2 ( PSEN2 ), amyloid precursor protein ( APP ) and prion protein genes ( PRNP ) for patients resident in the UK in a 5 year period. The variation in the incidence of mutation detection between UK regions was assessed with census population data. Published studies of the genetic epidemiology of familial early onset AD (EOAD) were reviewed to produce estimates of the number of patients in the UK that should be detected. Results: The rate of detection of EOAD and IPD varied very significantly and consistently between regions of the UK with low rates of detection in Northern and Western Britain (72% less detection in these regions compared with Central and Southeast Britain). The estimates from population studies further suggest a greater number of patients with EOAD than are diagnosed by genetic testing throughout the UK. Conclusions: It is likely that patients with EOAD and IPD are not being recognised and referred for testing. With the prospect of meaningful disease modifying therapeutics for these diseases, this study highlights an issue of relevance to neurologists and those planning for provision of National Health Services.